Parthenium hysterophorus Herbage Mulching: a Potential Source of Weeds Control in Soybean (Glycine max) - SIDDIQUI,M.H. (2018)
ABSTRACT: Weeds have indirect effects on crop plants. Crop development is affected by allelopathy from certain weed species. Allelochemicals from allelopathic weeds can disturb the root and shoot growth of emerging crop seedlings, as well as cause several other types of damage. A study was carried out to investigate the allelopathic potential of Parthenium hysterophorus for weed response in soybean. The experiment was laid out in Randomized Complete Block Design (RCBD) with split plot arrangements and replicated thrice. Sowing methods (broadcast and line sowing) were kept in the main plot and mulching treatments (surface mulching and soil incorporation) were kept in the sub-plots. Mulching of Parthenium hysterophorus was applied at the rate of 1.0 t ha-1, 2.5 t ha-1, 5 t ha-1 with control (no parthenium). Manual weed control was also used as treatments. The results revealed that significantly higher shoot length, shoot fresh weight, shoot dry weight, root length, root fresh weigh, root dry weight, number of nodules per plant, nodules fresh and dry weight, number of branches, number of pods per plant, thousand seed weight biological yield, economic yield, dry matter yield and harvest index were recorded with the soil incorporation of Parthenium herbage at the rate of 2.5 t ha-1. Maximum weed density and weed dry biomass were recorded in control plots while weed control efficiency was seen greater in plots where Parthenium herbage was applied to surface at the rate of 5 t ha-1. The results suggested that the use of Parthenium hysterophorus herbage mulching can reduce infestation of weeds by its allelopathic effects and increase the yield of soybean under sub-humid agro-climatic conditions.